The Potential Profitability of Poultry Farm: A Case of Mini Poultry Farm Feasibility of Tawi-Tawi Regional Agricultural College: Tarawakan Campus - Puhagan, Edwin M; Juljani, Nurshima H (International Journal of Membrane Science and Technology, 2023)
It was a school-based research project examining the viability of a farm producing Mini-Poultry broilers on the Tawi-Tawi Regional Agricultural College Tarawakan campus. As input costs and point-of-sale prices changed, potential profitability was assessed using sensitivity analysis. This was decided based on the growth rate, survival, and return on investment of the grown chicken. Running down the data using Statistics for Applied Science (SAS) produced a P-value of 0.131927, showing a linear trend with a minor deviation. As the number of chicks rises, profitability generally rises as well, or it stays the same if the quantity is maintained. This practical study boosts the output and incomes of locals who sell live chicken meat. It also continuously contributes to improving local bird production as it creates supplemental feed at its own feed mill using increasingly inventive techniques and primarily local products. As an alternative to expensive feed sold by feed millers, which has a lower "nutrient density" balanced for all nutrients but low energy due to the inclusion of low-energy ingredients like cassava leaf meal, acacia fruit meal, and swam cabbage mixed with commercial broiler diets, the small flocks of poultry are fed on "Domestic but improvised Feed." Due to the increased demand for meat with very small starting flocks that are then sold for growth under the traditional extensive system achieved by better health care, backyard village poultry flock producers are now transitioning into relatively small-scale or mini poultry chicken producers